Physicochemical, textural, and protein digestibility properties of extruded meat analogs prepared from rice bran protein concentrate and black soybean (Glycine max L. cv. Tudela) - Balonga, Bernadeth P. (Philippine Journal of Science, 2023)
Soybean is one of the most utilized raw materials in developing plant-based meat alternatives mainly because of its high protein content at a low cost. However, in terms of protein quality, it lacks sulfur-containing amino acids (cysteine and methionine), which limits its use as a complete protein source for substituting meat. Protein from rice bran contains a significant amount of cysteine and methionine; hence, this study aimed to develop meat analogs from black soybean (cv. Tudela) flour (S), rice bran protein concentrate (RP), and their blend (SRP) through single-screw extrusion using a two-way factorial in a completely randomized design. Single-screw extrusion is the cost-effective alternative to the widely used twin-screw extrusion. Results from the analyses on physicochemical [proximate composition, color values, pH, nitrogen solubility index (NSI), and amino acid analysis] and functional [water absorption capacity (WAC) and oil absorption capacity (OAC)] properties of the developed products revealed that at p < 0.05, products from S and RP blend have functionality with potential for a wider range of food applications than when S and RP are extruded separately. Amino acid analysis also revealed that combining RP with S increased the amount of sulfur-containing amino acids by 130.17%. Protein digestibility of products was as follows: S at 88.50%, SRP at 81.81%, and RP at 73.86%, respectively; with oil modification of the feed formulations to 20%, the protein digestibility significantly improved to as follows: S at 96.62%, SRP at 85.89%, and RP at 93.83% at p < 0.05. Extruded S and SRP have texture profiles comparable to chicken and extruded RP to pork. Results from this study may provide base data for the formulation of plant-based meat alternatives with improved protein quality and meat-like texture.